Reimbursements of The Application of Google Classroom by University Scholars for Learning Vocational and Entrepreneurship Courses - Amos Ochayi Onojah; Omotayo Olabo Obielodan; Adekola Musiliu Aderoju; Adenike Aderogba Onojah; Boluwatife Joshua Adigun (MO.RI Publishing, 2021)
Google classroom had been used for instructional delivery of courses at all levels of education with tertiary institution inclusive. The use of these technologies had their merits as well as their demerits. This study investigates the reimbursement of Google classroom by undergraduate students for learning vocational and entrepreneurship courses. This study employs the survey method and 250 undergraduate students were purposively sampled. The findings established that Google classroom is very useful for learning vocational and entrepreneurship courses. Gender had no significant influence on the reimbursements of undergraduates’ utilization of google classroom for learning vocational and entrepreneur courses but academic level had significant influence. The study concluded that there could be tremendous increase in lecturers job performance as well as students’ academic performance if Google classroom is employed for lectures.